¨Mejoramiento de la durabilidad de materiales compuestos FRCM reforzados con fibras de cabuya, evaluando las propiedades a tracción y adherencia ¨ - López Quishpe, Edgar Mauricio (2017)
The implementation of reinforcing techniques to structural elements with strength problems, due to the quality of concrete or lack of steel reinforcement, helps to avoid unnecessary demolitions of constructions. Nowadays, there are several types of reinforcement; one of the most common techniques for reinforcement is based on the use of FRP (Fiber Reinforced Polymer) composites, which are made of polymer matrices reinforced with fibers. These materials present problems at high temperatures and are produced in a way that affects the environment. Currently, a new method for reinforcing structures is being developed, which is known as FRCM (Fabric Reinforced Cementitious Matrix) composites. This material is produced with a cementitious matrix reinforced with layers of natural fiber fabrics. One of the main problems related to use of natural fibers as FRCM reinforcement is the durability issues, since when working with a cementitious material, there is chemical incompatibility due to the high alkalinity of the cement water that causes porosity in the matrix around the fibers, accumulating calcium hydroxide (Ca (OH)2). With the presence of Ca (OH)2, and an increased temperature, it is observed a noticeable acceleration of the degradation in the sisal fibers, losing durability and adherence between the FRCM material and the substrate element or between the matrix and the fabric. Consequently, this thesis is aimed at studying how the durability of FRCM composite materials reinforced with sisal fibers could be improved. According to this objective, different cementitious matrices were studied and some tests were carried out, such as: tensile test on single yarns, adherence tests on fabric samples embedded in the matrices and pull-off tests to study FRCM detachment. All the tests were performed subjecting the fiber samples embedded in the matrices to variable environmental conditions for up to eight months. Another parameter in this research was the type of treatment that could be used to prevent accelerated aging in the fibers. Both the use of lime as a blocking agent and the use of a polyester resin as a coating of the fibers were considered. The results reveal that the use of resin to coat the fabrics together with the use of a cementitious matrix modified with natural pozzolanas, greatly help to improve the durability of FRCM composites reinforced with sisal fibers.